Desarrollo de un endulzante natural a base de yacón (Smallanthus Sonchifolius) dirigido a personas con limitaciones en la ingesta de azúcar convencional y propuesta para su proceso de producción (2022)
The production of a sweetener based on the extraction of yacon syrup, not only aims to be part of the product options that replace sugar, but also to be a food that contributes considerably to the daily diet of consumers, according to the benefits that the tuber (Smallanthus Sonchifolius) can provide naturally, such as the release of substances with inhibitory power of metabolic processes that include the release of glycosides and acids that precede the processes that trigger insulin disorders.